1989
DOI: 10.1128/jb.171.7.3961-3967.1989
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide mutants of Rhizobium meliloti are not defective in symbiosis

Abstract: Mutants of Rhizobium meliloti selected primarily for bacteriophage resistance fall into 13 groups. Mutants in the four best-characterized groups (class A, lpsB, lpsC, and class D), which map to the rhizobial chromosome, appear to affect lipopolysaccharide (LPS) as judged by the reactivity with monoclonal antibodies and behavior on sodium dodecyl sulfate-polyacrylamide gels of extracted LPS. Mutations in all 13 groups, in an otherwise wild-type genetic background, are Fix+ on alfalfa. This suggests that LPS doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 48 publications
2
42
1
Order By: Relevance
“…It is perhaps not surprising that exoB is not regulated by exoR and exoS because exoB mutants are also defective for the production of a second exopolysaccharide, EPS II (13,41), and show lipopolysaccharide alterations (4,18). Recently it has been shown that the exoB gene encodes UDP-galactose epimerase, which converts UDP-glucose to UDP-galactose (3a olism [1], and therefore exoB mutants are not galactose sensitive.)…”
Section: Resultsmentioning
confidence: 99%
“…It is perhaps not surprising that exoB is not regulated by exoR and exoS because exoB mutants are also defective for the production of a second exopolysaccharide, EPS II (13,41), and show lipopolysaccharide alterations (4,18). Recently it has been shown that the exoB gene encodes UDP-galactose epimerase, which converts UDP-glucose to UDP-galactose (3a olism [1], and therefore exoB mutants are not galactose sensitive.)…”
Section: Resultsmentioning
confidence: 99%
“…Although R. meliloti that are deficient in LPS induce Ng-fixing nodules on alfalfa (Clover, Kieber & Signer, 1989), Ips mutants of R. leguminosarum bv. viciae elicit nodules on pea or vetch, which, while appearing to be normal overall, are Fix because the rhizobia are not released from the infection threads (Priefer, 1989;Brewin et al, 1990).…”
Section: Infectionmentioning
confidence: 99%
“…a genus of gram-negative soil bacteria, have been described that are unable to penetrate the root hair cells of RAETZ legumes (116,117). In some of these mutants there are alterations in the composition of O-antigen (116).…”
Section: Biochemistry Of O-antigensmentioning
confidence: 99%